2017
DOI: 10.1021/acs.est.7b04940
|View full text |Cite
|
Sign up to set email alerts
|

A Case Study Application of the Aggregate Exposure Pathway (AEP) and Adverse Outcome Pathway (AOP) Frameworks to Facilitate the Integration of Human Health and Ecological End Points for Cumulative Risk Assessment (CRA)

Abstract: Cumulative risk assessment (CRA) methods promote the use of a conceptual site model (CSM) to apportion exposures and integrate risk from multiple stressors. While CSMs may encompass multiple species, evaluating end points across taxa can be challenging due to data availability and physiological differences among organisms. Adverse outcome pathways (AOPs) describe biological mechanisms leading to adverse outcomes (AOs) by assembling causal pathways with measurable intermediate steps termed key events (KEs), the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 64 publications
0
34
0
Order By: Relevance
“…For risk assessment, the AOP framework can only be used when linked with toxicokinetic data or as suggested by Escher and coworkers linking the AOP to the exposome and aggregate exposure pathways (AEPs) (see Figure ). In a case study, Hines and coworkers showed that AEPs indeed can be beneficial to human risk assessment . Quantitative AOPs were proposed by Conolly and coworkers and extend the concept of AEPs by including dose‐ and time‐response information …”
Section: Adverse Outcome Pathwaysmentioning
confidence: 99%
“…For risk assessment, the AOP framework can only be used when linked with toxicokinetic data or as suggested by Escher and coworkers linking the AOP to the exposome and aggregate exposure pathways (AEPs) (see Figure ). In a case study, Hines and coworkers showed that AEPs indeed can be beneficial to human risk assessment . Quantitative AOPs were proposed by Conolly and coworkers and extend the concept of AEPs by including dose‐ and time‐response information …”
Section: Adverse Outcome Pathwaysmentioning
confidence: 99%
“…While there is a lot of information on exposure potentially available in the scientific literature, a structured way to collect exposure information at different levels is missing. Analogous to the AOP concept, the AEP framework has been proposed to collect all relevant information of environmental fate and exposure of chemicals and stressors through the environment up to the individual or population (Teeguarden et al 2016;Hines et al 2018). It is specifically designed for organizing exposure data from multiple sources, enabling that information is readily available, and highlighting data gaps and uncertainties (Hines et al 2018).…”
Section: Aggregate Exposure Pathway (Aep) Frameworkmentioning
confidence: 99%
“…The AEP starts with the chemical(s) release into the environment from a source up to the Target Site Exposures (TSEs). The AEP consists of two entities: a Key Exposure State that describes the amount of a stressor at a given location and time, and a Key Transitional Relationship that describes either the transport of that stressor to a different location or the transformation of that stressor into a different molecule (Hines et al 2018). Individual AEPs can be assembled into AEP networks to characterize the movement of multiple chemicals and transformations from one chemical to another (Hines et al 2018).…”
Section: Aggregate Exposure Pathway (Aep) Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…How best to achieve this is still the subject of debate. However, there is a growing consensus that AOPs will best serve toxicology if methods can be found to integrate an appreciation of dose–response relationships and toxicokinetics with AOPs to build the concept of ‘source to outcome pathways’ that seek to embrace the totality of the processes involved in an aggregate exposure pathway (AEP) (Teeguarden et al 2016 ; Vinken and Blaauboer 2016 ; Hines et al 2018 ). Such a development will be of critical importance in consolidating AOPs as tools for risk assessment as well as hazard identification.…”
Section: The Future Trajectory Of Aopsmentioning
confidence: 99%